1999
DOI: 10.1002/(sici)1097-4628(19991209)74:11<2681::aid-app16>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical evaluation of propylene polymers under static and dynamic loading conditions

Abstract: ABSTRACT:The present investigation is concerned with the evaluation of the impact toughness of commercial-grade Propylene polymers. Conventional impact static stressstrain and static fracture experiments were carried out. Static stress-strain experiments revealed different pattern behaviors among the materials that were reflected in the fracture behavior. Under static conditions, all materials exhibited ductile behavior and crack grew under J-controlled conditions displaying stress whitening through the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
0
16
1
Order By: Relevance
“…The influence of the structural and morphological parameters (content, size and interparticle distance of the rubber modifiers [4][5][6][7][8][9][10][11][12][13][14], molecular weight, tacticity, crystallinity index, shape, size and distribution of crystalline regions of the PP matrix) on the fracture behaviour of PPs has been widely analyzed specially under high loading rates and at low temperature [2][3][4][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The main reason is that these polymeric materials, especially the block copolymers, exhibit a wide range of properties and structures with a great performance in the high strain field.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of the structural and morphological parameters (content, size and interparticle distance of the rubber modifiers [4][5][6][7][8][9][10][11][12][13][14], molecular weight, tacticity, crystallinity index, shape, size and distribution of crystalline regions of the PP matrix) on the fracture behaviour of PPs has been widely analyzed specially under high loading rates and at low temperature [2][3][4][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The main reason is that these polymeric materials, especially the block copolymers, exhibit a wide range of properties and structures with a great performance in the high strain field.…”
Section: Introductionmentioning
confidence: 99%
“…Santarelli and Frontini showed that it was very difficult to determine the fracture toughness of PP homopolymers at room temperature and under static loading conditions [28]. The fracture toughness data were highly scattered and showed a strong sensitivity to notch [19][20][21][22][23][24][25][26][27][28][29][30][31] and geometry dimensions [4,5,28] and strain rate [5,12,15,16,30,31]. In addition, some [4,12,19,33,34,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In load bearing and engineering applications for both PP and PE, an improved understanding of fracture behavior along with general strength analysis is considered necessary as it provides information on the crack growth process in the materials that can be directly relevant to their performance in real-world conditions [12]. Fracture toughness measurements using different fracture mechanics approaches and the identification of crack propagation mechanisms have been investigated by previous researchers [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], both for PP and PE, with the research focusing on injection or other molding processes. This type of detailed material analysis is still absent for rotationally molded PE and PP however.…”
Section: Introductionmentioning
confidence: 99%
“…For co-polymers, cavitation in the copolymer particles, shear yielding, microvoiding, and crazing were identified as the deformation mechanisms [18]. To investigate the effects of morphological parameters on fracture behavior and toughness properties, Charpy or Izod impact strength tests have also been conducted in the literature [19,[30][31][32]. The crystal structure, elastomeric content present in the copolymer, molecular weight, and so on are all believed to have an effect on the fracture toughness properties of PP [13,18,19,30,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%